Social research : a practical introduction - Curtis, Bruce (SAGE Publications, 2011)
"Original, fresh, and relevant this is a theoretically-informed practical guide to researching social relations. The text provides a mixed methods approach that challenges historical divisions between quantitative and qualitative research. It adopts a multidisciplinary approach to social science research, drawing from areas such as sociology, social psychology, and social anthropology. Explicitly addressing the concerns of emergent researchers it provides both a 'how to' account of social research and an understanding of the main factors that contextualize research by discussing 'why do' social scientists work this way. Throughout the twelve comprehensive chapters procedural (how to) accounts and contextual (why do) issues are usefully applied to major themes and substantive questions. These key themes include research design; the practices of research and emergent researchers: beyond ontology, epistemology and methodology; the impact of technology on research; and putting the research approach in context. A superb teaching text this book will be relished by lecturers seeking an authoritative introduction to social research and by students who want an accessible, enriching text to guide and inspire them."--Publisher's website.